2002
DOI: 10.1111/j.1553-2712.2002.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer-assisted Prescription Writing on Emergency Department Prescription Errors

Abstract: Computer-assisted prescriptions were more than three times less likely to contain errors and five times less likely to require pharmacist clarification than handwritten prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…These changes included CPOE, along with referring patients for high-risk elective procedures based on evidence of quality and outcomes, and staffing intensive care units with boardcertified intensivist physicians (26). One study found that prescriptions written using CPOE were three times less likely to contain errors and five times less likely to require pharmacist clarification compared to those handwritten (27). In EDs that have incorporated CPOE, it has been preferred over paper versions, especially by resident physicians.…”
Section: Computerized Physician Order Entrymentioning
confidence: 95%
“…These changes included CPOE, along with referring patients for high-risk elective procedures based on evidence of quality and outcomes, and staffing intensive care units with boardcertified intensivist physicians (26). One study found that prescriptions written using CPOE were three times less likely to contain errors and five times less likely to require pharmacist clarification compared to those handwritten (27). In EDs that have incorporated CPOE, it has been preferred over paper versions, especially by resident physicians.…”
Section: Computerized Physician Order Entrymentioning
confidence: 95%
“…In this high-tech electronic world, a computerized medication ordering system should show immediate benefits by preventing "never events" and reducing the 1.5 million errors entered annually [9,10]. The problems of illegible handwriting, misplaced charts, and carelessness that were assumed to be responsible for 7000 deaths per year with paper charting have been replaced with a new set of errors during CPOE implementation [4,9,11,12]. Since going live, CPOE has shown a new collection of errors that are still being identified as researchers investigate the new electronic system and how it interacts with health care providers in the hospital setting [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…The IOM's To Err is Human defined the abundance of medication order errors (OEs) and paper charting errors that compromise patient safety while exaggerating health care costs [1e4]. It concluded that these errors could be prevented by the introduction of EMRs [4,5]. EMR was instituted to streamline, simplify, and unify patient care throughout the country, which is something paper charting could not contend with [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…One suggested approach to prevent medication errors is to use computerized drug prescribing support systems. However, computer-assisted prescribing represents a new tool in the practice of emergency medicine and it is not well understood and has not been evaluated yet (Bizovi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%